Training in different brushing techniques in relation to efficacy of oral hygiene in young adults: a randomized controlled trial. (5th February 2016) - Harnacke, Daniela; Stein, Kathrin; Stein, Patrick; Margraf‐Stiksrud, Jutta; Deinzer, Renate
Abstract: Aim: This study aims to assess plaque scores after oral hygiene in an unselected sample of young German adults and to compare the effects of computer‐based training of the Fones versus the modified Bass technique on these scores. Material and Methods: Seventy 18‐ to 19‐year olds received computer‐based training of the Fones technique, the modified Bass technique or basic instructions of oral hygiene alone (control group). The marginal plaque index (MPI; percentage of sections adjacent to the gingiva showing plaque) and BOP were assessed at baseline and after 6, 12 and 28 weeks. MPI was assessed immediately after participants had been asked to perform oral hygiene to the best of their abilities. Results: At baseline, MPI levels of 83.3% ± 12.5 (mean ± SD) were observed. After 12 weeks, groups differed significantly ( p < 0.05) with respect to MPI: Fones group: 70.3% ± 14.7; Bass group: 77.91 ± 14.37; control group: 79.3% ± 9.2. No differences in BOP were found. Conclusions: High plaque levels at gingival margins after oral hygiene were observed in an unselected sample of young German adults. After 12 weeks, plaque levels after oral hygiene were slightly reduced in the group who had received training of the Fones technique but effects trailed off afterwards. The study failed to prove effects of the training on signs of gingival inflammation.